Hubungan Ketersediaan Fasilitas Dan Sumber Daya Manusia Dengan Waktu Tunggu Pasien - Jumlaida Dinst; Hi Suwandi Luneto; Rahmat Hidayat Djalil (STIKES Columbia Asia Medan, 2025)
The emergency department (ED) is the frontline of the hospital that provides health care tp patients the hospital that provides health care to patients who experience emergency conditions. The principle of service in the emergency room is fast and timely, but the increase in the the number of patients visiting the emergency room and the availability of inadequate resources can result in patient waiting time. This study is known to know the relationship between the availability of facilities and human resources with patient waiting time in the emergency department installation. This study is an observational analytic study with a cross sectional study research design. Data collection using SAP and questionnaire sheets. For the analysis test using chi-square with a level of significance (a <0.05). The chi-square statistical test obtained a value ≤ p +(a <0.005). From this study, there is a relationship between the availability of facilities and human resources with patient waiting time in the emergency room.